2017
DOI: 10.7860/jcdr/2017/27207.9907
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Study on Dermatoses in Pregnancy

Abstract: INTRODUCTIONPregnancy, an endocrine storm, is characterized by altered endocrine, metabolic, and immunologic milieus. These alterations result in both multiple physiologic and pathologic cutaneous changes that may range from normal cutaneous changes to eruptions that appear to be specifically associated with pregnancy [1]. Moreover, pregnancy may modify the course of a number of dermatological conditions. The present study was undertaken to find out the prevalence of the physiological and pathological skin cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
5
14
0
7
Order By: Relevance
“…Other conditions such as scabies, Taenia Cruris, Miliaria, and Intertrigo etc were coexisting in pregnant mothers. Similar skin conditions in pregnancy were found in many studies 2,3 . The disease conditions might occur coincidentally or sometimes as increased glandular functions, raised levels of estrogen etc.…”
Section: Discussionsupporting
confidence: 67%
“…Other conditions such as scabies, Taenia Cruris, Miliaria, and Intertrigo etc were coexisting in pregnant mothers. Similar skin conditions in pregnancy were found in many studies 2,3 . The disease conditions might occur coincidentally or sometimes as increased glandular functions, raised levels of estrogen etc.…”
Section: Discussionsupporting
confidence: 67%
“…Increased prevalence of pigmentary changes during pregnancy is related to increased alpha-melanocyte stimulating hormone plasma concentration as well as melanocytic stimulation caused by estrogens and progesteron [10]. Kannambal et al [1] reported pigmentary changes in 90.8%, Fernandes et al [7] observed hyperpigmentation in 87,95% of cases, Panicker et al [6] reported hyperpigmentation in 87.6% of the studied women. In our group it is difficult to refer to the incidence of pigmentary changes because none of the interviewed women reported discoloration as a skin problem.…”
Section: Resultsmentioning
confidence: 98%
“…Pregnancy is a life period connected with various and intensive endocrine, metabolic, immunological and vascular changes in women's bodies. Regarding the skin, these conditions may range from physiological changes, common skin diseases not associated with pregnancy, to pathologic eruptions specially associated with pregnancy [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desta forma, estas necessitam de atenção por parte dos profissionais de saúde, visto que, esta enfermidade se não for diagnosticada e tratada precocemente leva as incapacidades físicas. [7][8] Diante dos fatos, o presente estudo teve como questão norteadora: quais as características demográficas, sociais e clínicas de mulheres em idade fértil atingidas pela hanseníase em uma capital do nordeste brasileiro? As pesquisas vêm apontando um maior número de casos em mulheres na faixa etária reprodutiva.…”
unclassified